Impact of region of interest (ROI) size on the diagnostic performance of shear wave elastography in differentiating solid breast lesions. (June 2018) - Moon, Jin Hee; Hwang, Ji-Young; Park, Jeong Seon; Koh, Sung Hye; Park, Sun-Young
Background: Shear wave elastography (SWE) using a region of interest (ROI) can demonstrate the quantitative elasticity of breast lesions. Purpose: To prospectively evaluate the impact of two different ROI sizes on the diagnostic performance of SWE for differentiating benign and malignant breast lesions. Material and Methods: A total of 154 breast lesions were included. Two types of ROIs were investigated: one involving an approximately 2-mm diameter, small round ROIs placed over the stiffest area of the lesion, as determined by SWE (ROI-S); and another ROI drawn along the margin of the lesion using a touch pen or track ball to encompass the entire lesion (ROI-M). Maximum elasticity (Emax ), mean elasticity (Emean ), minimum elasticity (Emin ), and standard deviation (SD) were measured for the two ROIs. The area under the receiver operating characteristic curve (AUC) as well as the sensitivity and specificity of each elasticity value were determined. Results: The AUCs for ROI-S were higher than those for ROI-M when differentiating benign and malignant breast solid lesions. The Emax, Emean, Emin, and SD of the elasticity values for ROI-S were 0.865, 0.857, 0.816, and 0.849, respectively, and for ROI-M were 0.820, 0.780, 0.724, and 0.837, respectively. However, only Emax ( P  = 0.0024) and Emean ( P  = 0.0015) showed statistically significant differences. For ROI-S, the sensitivity and specificity of Emax were 78.8% and 84.3%, respectively, and those for Emean were 80.8% and 81.4%, respectively. Conclusion: Using ROI-S with Emax and Emean has better diagnostic performance than ROI-M for differentiating between benign and malignant breast lesions.